Ghetto : the history of a word - Schwartz, Daniel B., 1974- (Harvard University Press, 2019)
Few words are as ideologically charged as "ghetto." It was initially synonymous with two cities: Venice, where the word was first used in conjunction with the segregation of the Jews in 1516, and Rome, where the ghetto survived as a compulsory institution until the fall of the Papal States in 1870, long after it had ceased to exist elsewhere. Ghetto: The History of a Word offers a fascinating account of the changing nuances of this slippery word, from its coinage to the present day. It details how the ghetto emerged as an ambivalent metaphor for "premodern" Judaism in the nineteenth century and how it was later revived to refer to everything from densely populated Jewish immigrant enclaves in modern cities to the hyper-segregated holding pens of Nazi-occupied Eastern Europe. We see how this ever-malleable word traveled across the Atlantic Ocean, with pit stops on New York's Lower East Side and Chicago's Near West Side until it came to be more closely associated with African Americans than Jews. Chronicling this sinuous trans-Atlantic odyssey, Daniel B. Schwartz reveals the history of ghettos to be part of a larger story of struggle and argument over the meaning of a name. Paradoxically, the word "ghetto" came to loom larger in discourse about Jews when Jews no longer were required to live in legal ghettos. At a time when the Jewish associations have been largely eclipsed, Ghetto retrieves the history of a dangerously resilient word.--